Strategi Pembelajaran Everyone Is Teacher Here Untuk Membentuk Berpikir Kritis Pada Pembelajaran Pendidikan Agama Islam Siswa SMK Negeri 1 Wonosobo - Fina Syifaul Mawaddah; Mukromin Mukromin; Faisal Kamal (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The education sector requires innovation to prepare students to become competent individuals and to produce high-quality individuals in society by equipping them with various 21st-century skills to meet the demands of changing times. Through the everyone is teacher here learning strategy, it is hoped that students can develop critical thinking skills, which are highly essential in the current era of globalization.This research aims to explore how the everyone is teacher here learning strategy is implemented in SMKN 1 Wonosobo, its impact on fostering critical thinking, the factors influencing its implementation, and the outcomes after its execution. This study employs a descriptive qualitative research method. Data collection techniques include observation, interviews, and documentation, while data analysis involves triangulation.The findings reveal that the Islamic Education teachers at SMKN 1 Wonosobo have effectively implemented the everyone is teacher here learning strategy. The cultivation of students' critical thinking skills has started to progress well, although there are indicators that need reinforcement due to some students' lack of concentration in receiving new material. Supportive factors for the